(untitled) (Environmental Smoke, 2021)
Analyses the scientific production in Information Science field about the coronavirus/COVID-19 subject. It has as general objective to analyse the initiatives and publications made on coronavirus topic in the field of Information Science. It has as specific objectives: to map the main journals used to communicate research; to identify the most active programs or institutions and to recognize prominent authors. It uses an exploratory methodology, with a quantitative approach. It seeks theoretical support in bibliometrics and scientometrics. Reveals the high production of the field on the subject. Detects the first results dating from 2005, related to severe acute respiratory syndrome (SARS). Perceives the explosion in field production on the theme from 2020. It shows the highlight of the Journal of the American Medical Informatics Association, from the United States, and the Profesional de la Informacion, from Spain, with 49 and 47 results, respectively. It observes the high productivity of American authors, presenting twice as much the results of the Spanish authors, who are in second place in number of results. It shows the greater appearance of American financing agencies compared to other nationalities. Perceives the prominence in productivity, among the institutions, of the researchers of the University of London, of England. Reveals the highlight of the authors CONBOY, K .; DA CUNHA, M. B .; DWIVEDI, Y. K .; PAN, S. L .; PARKER, R. M. and WANG, H., with three results each. Among the Brazilian authors, the predominance of publications made in the journal AtoZ New Practices in Information and Knowledge and the greater link with brazilian institutions in comparison with foreign institutions is evident.